1999
DOI: 10.1523/jneurosci.19-01-00456.1999
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Sexual Behavior and Enhanced Dopamine Efflux in the Nucleus Accumbens of Male Rats afterd-Amphetamine-Induced Behavioral Sensitization

Abstract: Behavioral sensitization caused by repeated and intermittent administration of psychostimulants, such as cocaine and D-amphetamine, is accompanied by enhanced function in limbic-motor circuitry that is involved in the generation of motivated behavior. The present microdialysis study investigated the effect of D-amphetamine-induced sensitization on dopamine (DA) efflux in the nucleus accumbens (NAC) of male rats during sexual behavior. Male rats were given one injection of D-amphetamine (1.5 mg/kg, i.p.) or sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
63
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(77 citation statements)
references
References 50 publications
9
63
1
Order By: Relevance
“…An environment paired with repeated morphine injections can facilitate sexual behavior in male rats (Mitchell and Stewart, 1990a,b). Amphetamine pretreatment also facilitates sexual behavior in sexually naive male rats and is correlated with augmented dopamine release in the nucleus accumbens (Fiorino and Phillips, 1999). c-Fos expression was analyzed in the nucleus accumbens after amphetamine treatment.…”
Section: Sexual Experience Effects On Amphetamine-induced Locomotor Amentioning
confidence: 99%
See 1 more Smart Citation
“…An environment paired with repeated morphine injections can facilitate sexual behavior in male rats (Mitchell and Stewart, 1990a,b). Amphetamine pretreatment also facilitates sexual behavior in sexually naive male rats and is correlated with augmented dopamine release in the nucleus accumbens (Fiorino and Phillips, 1999). c-Fos expression was analyzed in the nucleus accumbens after amphetamine treatment.…”
Section: Sexual Experience Effects On Amphetamine-induced Locomotor Amentioning
confidence: 99%
“…In other words, the dopamine neurons previously sensitized to one drug will exhibit sensitized responses to another drug given for the first time (Cunningham and Kelley, 1992;Pierce and Kalivas, 1997a;Birrell and Balfour, 1998;Taylor and Horger, 1999). In addition to cross-sensitization among drugs, several studies have reported cross-sensitization between repeated exposures to pharmacological agents and natural motivated behaviors (Mitchell and Stewart, 1990a,b;Tidey and Miczek, 1997;Fiorino and Phillips, 1999). Therefore, we examined whether sexually experienced and sexually naive animals would respond differently to a novel stimulus known to activate dopamine pathways (i.e., cross-sensitization), such as amphetamine.…”
mentioning
confidence: 99%
“…[1][2][3][4] Once established, behavioural sensitization is often accompanied by enhanced dopamine (DA) release in the nucleus accumbens (NAcc). [5][6][7] Whereas terminal regions of the mesocorticolimbic DA system are clearly implicated in the long term expression of druginduced sensitization, 8 its induction and initial maintenance depends on modulation of synaptic events in close proximity to DA-containing neurons in the ventral tegmental area (VTA). [8][9][10] The enduring neural adaptations that accompany repeated exposure to drugs of abuse have been linked to specific forms of synaptic plasticity, including long-term potentiation (LTP) and long-term depression (LTD).…”
Section: Introductionmentioning
confidence: 99%
“…The neural circuits implicated in the processing of these vital components of decision making, including dopamine and cortical systems, continue to develop throughout the adolescent period (3,20). Previous work assessing the consequences of drug use on future reward processing has shown that a history of drug exposure may alter neural and behavioral responses to natural rewards, effects thought to be mediated by dopamine systems (21). A corruption of reward valuation could promote maladaptive and suboptimal behavior by placing excessive priority on seeking rewards such as food, drugs, or sex.…”
mentioning
confidence: 99%